Peak vertical jump power as a marker of bone health in children - Baptista, F.; Mil-Homens, P.; Carita, A. I.; Janz, K.; Sardinha, L. B. (International Journal of Sports Medicine, 2016)
The objective of this investigation was to evaluate the accuracy of peak vertical jump power (VJP) to identify children with bone mineral density (BMD) below average, defined as BMD measured by DXA and adjusted for body height at the whole body less head=- 1.0 standard deviation (SD). The sample included 114 boys and girls aged 8.5±0.4 years old. VJP was estimated from a countermovement jump performed on a contact mat using the measured flight time to calculate the height of rise of the center of gravity. Logistic regression analysis revealed that the odds ratio of having BMD=1.0 SD decreased 1.2% per watt of power and the probability of BMD below average was 75.6% higher in boys than in girls with the same peak power jump. Receiver operating characteristic analysis showed that the best trade-off between sensitivity and specificity to identify children with BMD<- 1.0 SD was 635 watts in boys (sensitivity=63.3%; specificity=69.2%; AUC=0.816, 95% CI: 0.681-0.95; p<0.001) and 515 watts in girls (sensitivity=75.0%; specificity=77.0%; AUC=0.849, 95% CI: 0.698-0.999; p=0.002). These cut-off values correspond to a vertical jump of 19.9 cm and 20.5 cm in 8-year-old boys and girls, respectively. The VJP showed a reasonable sensitivity and specificity as well good discriminant ability to identify children with BMD below average.